2015
DOI: 10.1007/s11998-015-9692-1
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of superhydrophobic surfaces on FRP composites: from rose petal effect to lotus effect

Abstract: A simple method is reported for the preparation of superhydrophobic fiber reinforced plastic (FRP) surfaces with controlled adhesion. By simply adjusting the content of CaCO 3 and SiO 2 of surface coating, after surface treatment, we can obtain the different FRP surfaces with diverse morphologies. The results confirm that the FRP samples not only could achieve superhydrophobicity but also present huge differences in adhesive abilities. The microlens surface presents a strong sticky performance which can hold a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…To determine the type of superhydrophobic surface and thus the wetting regime, a simple test was performed by placing a sufficiently small droplet, 5 µl of H2O in this case, on the surface of the processed stainless steel and inverting it. If the droplet runs off easily, the Lotus effect is dominant; if the droplet stays attached to the surface, the Rose petal effect dominated due to the strong adhesion force caused by the Cassie-impregnating wetting regime [15]. The result of this test can be seen in Figure 2(d), clearly demonstrating the rose petal effect.…”
Section: Resultsmentioning
confidence: 85%
“…To determine the type of superhydrophobic surface and thus the wetting regime, a simple test was performed by placing a sufficiently small droplet, 5 µl of H2O in this case, on the surface of the processed stainless steel and inverting it. If the droplet runs off easily, the Lotus effect is dominant; if the droplet stays attached to the surface, the Rose petal effect dominated due to the strong adhesion force caused by the Cassie-impregnating wetting regime [15]. The result of this test can be seen in Figure 2(d), clearly demonstrating the rose petal effect.…”
Section: Resultsmentioning
confidence: 85%
“…Rose petal surfaces contain distinct features with dimensions that can be classified on at least two different scales (1 -13). The hierarchical roughness of these surfaces enables water droplets to penetrate into the void spaces between the larger, microscale structures while limiting further wetting and penetration of water into the surfaces with the inclusion of nanoscale hydrophobic features (3)(4)(5)(6)(7)(8)(9). The wetting properties of rose petal surfaces is a delicate balance between the Cassie-Baxter state (14) where a water droplet is supported on surfaces with entrapped air pocketsand the Wenzel state (15)where a water droplet is fully wetting the surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Applications in creating surfaces with an enhanced water resistance, improved capability of collecting water, and/or proficiency in maintaining moisture has inspired many researchers to prepare rose petal like surfaces. Many studies have demonstrated that the opposing water wetting states, namely hydrophobicity and hydrophilicity, of surfaces can be tuned by varying the dimensions of micro-and nanostructures (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). One method for preparing surfaces with well-defined structures uses reactive ion etching to prepare regular arrays of cylindrical silicon nanopillars (12).…”
Section: Introductionmentioning
confidence: 99%
“…Τα παραπάνω φαινόμενα έχουν ως αποτέλεσμα τον ιριδισμό(Kinoshita & Yoshioka 2005). Η μελέτη των πετάλων μπορεί να βοηθήσει στην κατανόηση της σχέσης μεταξύ επιφανειακών δομών και επιφανειακών ιδιοτήτων, οι οποίες με την σειρά τους παρέχουν μια κατεύθυνση βιομιμητικής μελέτης τόσο σε θεωρητικές όσο και πρακτικές προσεγγίσεις(Zhang et al 2012, Yeh et al 2014, Sun & Wang 2015, Kato et al 2015.Κατασκευάστηκαν βιομιμητικά πολυμερή υμένια διπλασιάζοντας την ιεραρχική δομή των πετάλων, τα οποία εμφανίζουν λειτουργίες δομικού χρώματος μόνο στο υπεριώδες φάσμα(Feng et al 2010). Αργότερα κατασκευάστηκαν αντίγραφα ανάλογα με την ιεραρχία των μικρο-και νανο-δομών του πετάλου του τριαντάφυλλου(Lee et al 2010).…”
unclassified